HAEMATOLOGICAL AND BIOCHEMICAL CHANGES IN LIONFISH (PTEROIS RUSSELII) VENOM TREATED SWISS ALBINO MICE - A.SUBRAMANIYAN; R.SARAVANAMURUGAN; P.SANGEETHA (International Journal of Pharma and Bio Sciences, 2016)
The effect of lionfish (Pterois russelii) venom was examined on certain biochemical and haematological parameters in experimental mice. Crude venom was extracted from the spines of lionfish. Mice blood (0.5ml) was collected before and after injection of the venom. The haematological parameters were determined by using Haemocytometer and biochemical markers were analyzed by Auto analyzer using diagnostic kits. Haematological changes were drastically decreased after 6 hours of injection of 3.75µg/kg b.w. (10% of the LD50 value) of the venom and were reduced till 24 hours and start to recover after 48 hours. Biochemical markers AST, ALT, ALP, LDH and CPK were increased after 6 hours of venom administration and were significantly high till 48 hours. Similarly, blood glucose and urea levels were also significantly increased after venom injection. On the other hand, no significant difference was observed in the total protein, creatinine and TG levels after venom injection. The cholesterol levels remain unchanged throughout the experimental period. This experimental result suggests that the venom has short term reversible effect in a mouse model at sub lethal dose.